Histological and parasitological distinctive findings in clinically-lesioned and normal-looking skin of dogs with different clinical stages of leishmaniosis - Ordeix, Laura (Parasit Vectors, 2017)
BACKGROUND: Normal-looking skin of dogs with leishmaniosis frequently shows microscopic lesions along with the presence of Leishmania amastigotes. However, histological lesions with or without detection of amastigotes might not occur in less severe clinical cases. In addition, comparative studies between paired clinically-lesioned and normal-looking skin samples from dogs with different disease severity are lacking. The objective of this study was to compare histological and parasitological findings by Leishmania immunohistochemistry (IHC) and quantitative PCR (qPCR) on paired clinically-lesioned and normal-looking skin biopsies from 25 dogs with different clinical stages of leishmaniosis, 11 with stage I-mild disease (papular dermatitis) and 14 with stage II-III (ulcerative or exfoliative dermatitis). RESULTS: The study demonstrated microscopic lesions in 14 out of 25 (56%) samples from normal-looking skin biopsies. In those samples, perivascular to interstitial dermatitis composed by macrophages with lymphocytes and plasma cells was observed mainly in the superficial and mid-dermis. The intensity of the dermatitis was mild to moderate and always less prominent than in the clinically-lesioned skin. In normal-looking skin samples, the presence of parasites was detected by histology, IHC and qPCR in 5/25 (20%), 8/25 (32%) and 18/25 (72%), respectively. Leishmania was encountered in 11/25 (44%), 23/25 (92%) and 25/25 (100%) of clinically-lesioned skin samples by histology, IHC and qPCR, respectively. Normal-looking skin from dogs with stage I-mild disease was less frequently inflamed (P = 0.0172). Furthermore, Leishmania was more easily demonstrated by histology (P = 0.0464), IHC (P = 0.0421) or qPCR (P = 0.0068) in normal-looking skin of dogs with stage II-III-moderate to severe disease. In addition, in the latter group, there was a significantly higher parasite load studied by means of qPCR than in dogs with less severe disease (P = 0.043). Clinically-lesioned skin from dogs with stage I disease was more frequently characterised by the nodular to diffuse pattern and granuloma formation (P = 0.0166) and by a lower parasite load studied by means of qPCR (P = 0.043) compared with more diseased dogs. CONCLUSIONS: Normal-looking skin from dogs with stage I is less likely to present histological lesions as well as harbour the parasite when compared with dogs with moderate to severe leishmaniosis.